Blood, guts, and grease : George S. Patton in World War I - Mikolashek, Jon (American warriors, 2019)
"Prior to World War I, George S. Patton was a lowly Lieutenant known more for his wealth than military ability. When the United Stated entered World War I, Patton joined General John J. Pershing's American Expeditionary Force (AEF) on the Western Front, where he was given the chance to prove his abilities. A driven and intrepid solider, Patton soon learned how to organize, command, and lead men in battle as the first tank commander in the US Army, and before long, his name became associated with armored warfare. Although the tank was a crude armored behemoth in 1918 with only a mixed record in battle, Patton personally oversaw the logistics of their first combat use by US forces and commanded the Light Tank Brigade during the Battle of Saint Mihiel, the attack into Pannes, and the Meuse Argonne Offensive. His successes during World War I laid the groundwork for not only his own personal future triumphs but also for the success of the entire US Army armored forces in World War II. In Blood, Guts, Grease and Oil: George S. Patton in World War I, Jon B. Mikolashek explores, for the first time, George S. Patton's World War I career and the role it played in his learning the art of command, how to lead large units of soldiers, and more importantly, how he would react to enemy fire. This work considers every aspect of Patton's trajectory from his relationship with Pershing to the selection of tanks for combat, from the creation of the Tank Corps and the Light Tank School to Patton's eventual successes and injuries in battle. Blood, Guts, Grease and Oil will reveal how the experience Patton gained in World War I was seminal in his development as a leader and laid the foundation for many of the attributes and characteristics he would later exhibit during World War II"--